EFFECTS OF RURAL AND URBAN POPULATION ON HEALTH CARE EXPENDITURE IN CHINA: ANALYSIS USING BOUND TESTING APPROACH - NurHaiza Nordin; NurNaddia Nordin; Nor Dalila Marican (Journal of Islamic, Social, Economics and Development, 2018)
This paper examines the effects of population at rural and urban on health careexpenditure in the case of China. Total population in China increased from year to year, as in1970 total population is 5.78 million to 1.21 billion in 2015. Projection of populationestablished in 2015 predict that the total population will keep growing until at least 2050,reaching an estimated 8 billion people in 2024, and 9 billion people in 2024 and 9 billion by2040. As the demographic transition follows its course worldwide, the population will agesignificantly, with most countries outside Africa trending towards a rectangular age pyramid.But total population in urban is higher than population in rural. For urban population theywill spend with their own money for healthcare or out of pocket expenditure. This paper isestimate the comparison between population in rural and urban on healthcare expenditure incase of China. By using bound testing approach to cointegration and error correction model,developed within an autoregressive distributed lag (ARDL) framework developed by Pesaranet al. (1999) and data cover from period 1970-2016, we investigate whether a long-runequilibrium relationship exists between population and health care expenditure. Using thisapproach, the expected result for long run relationship between population in rural and urbanon health care expenditure is positive but the healthcare expenditure for urban population ishigher than rural population.